Tatuoca Project: Automated data extraction from magnetogram images - Sales, Keanu Frota; Baldez, Raissa Moraes; Machado, Pericles Lopes; Abreu, Vinicius Augusto Carvalho de; Camperos-Reyes, Jacquelin Teresa; Zapata, Cristian Berrío; Martins, Cristiano Mendel (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2025: Anais Estendidos da XXXVIII Conference on Graphics, Patterns and Images, 2025)
The Earth’s magnetic field acts as a natural shield against solar radiation, with several magnetic observatories established around the world. Among them, the Tatuoca Magnetic Observatory, located in the equatorial region, stands out for the intense variations of the field in this area. Its 50 years of historical records are fundamental to the study of the Earth’s magnetic field. However, preserving these records faces significant challenges, as they degrade over time. To prevent this loss, the Tatuoca Project proposes the computerized extraction of data from these records and making this information available to the global scientific community. Using image processing and data analysis techniques, including clustering methods such as DBSCAN, the project aims to transform the physical records into accurate and accessible digital formats, as well as enabling automatic extraction, replacing the time-consuming manual work of data extraction.